Adaptation of Field Experience Practice Teachers in a School Impacted by the Earthquake and the Covid-19 Pandemic - Wahyuddin Wahyuddin (research, training and philanthropy institution Natural Aceh, 2023)
This study aimed to reveal how Teachers of Feld-Practice Program or PPL teachers adapted while teaching at SMA Negeri 1 Malunda, a school affected by the earthquake and the Covid-19 pandemic. Data was collected through reflective journals written every day by five PPL teachers. Reflective journals described PPL teachers’ experiences while teaching at SMAN 1 Malunda, including adaptations they made while on duty. In addition, a Focus Group Discussion was held after the PPL teacher assignment was completed to obtain additional information and some necessary data verification. Qualitative content and thematic analysis using NVivo 12 were implemented. Five phases passed in this analysis process: data import, coding, exploration, visualization, and data presentation. The finding of this study was that the PPL teachers at SMA Negeri 1 Malunda adapted through three stages, namely the period of observation, teaching preparation, and teaching actualization. Moreover, the PPL teachers believed that the earthquake and the Covid-19 pandemic simultaneously resulted in non-conducive educational activities in the school. The findings were significant for the PPL committee, school principals, and tutors in helping PPL students adapt and overcome the problems they face as new teachers.